PENDIDIKAN PERLINDUNGAN HUKUM USAHA MIKRO KECIL DAN MENENGAH (UMKM) DI DESA BANJARASRI GUNA MENINGKATKAN KESADARAN HUKUM BAGI PELAKU UMKM - Itok Dwi Kurniawan; Devi Aprilina; Josephine Morla Primaputri; Priscilla Wresty (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2021)
The problem in this community service activity is the lack of knowledge from the people of Banjarasri Village about the arrangements that can protect MSME actors. The purpose of this community service is to provide understanding to MSMEs in Banjarasri Village. This community service activity was carried out in the form of a webinar through a zoom meeting with MSME actors in Banjarasri Village. Submission of material with lecture methods and interactive question and answer. The presentation of the material is divided into two sessions, the first is about legal protection for MSMEs and the second is about the perspective of the Kulon Progo Regency Office of Micro, Small and Medium Enterprises Cooperatives. During the activity, participants were able to follow well, deliver material by speakers who were easily accessible, and participants actively asked questions to resource persons.